2010
DOI: 10.1007/s11255-010-9830-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of serum potassium concentration in dialysis-associated hyperglycemia and their correction with insulin: review of published reports

Abstract: The main difference between dialysis-associated hyperglycemia (DH) and diabetic ketoacidosis (DKA) or nonketotic hyperglycemia (NKH) occurring in patients with preserved renal function is the absence of osmotic diuresis in DH, which eliminates the need for large fluid and solute (including potassium) replacement. We analyzed published reports of serum potassium (K(+)) abnormalities and their treatment in DH. Hyperkalemia was often present at presentation of DH with higher frequency and severity than in hypergl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…This review presents an interpretation, based upon the actions of relevant regulators of internal potassium balance, of the cardinal findings in our review of published studies on serum K ? in DH and its treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…This review presents an interpretation, based upon the actions of relevant regulators of internal potassium balance, of the cardinal findings in our review of published studies on serum K ? in DH and its treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dialysis patients with hyperglycaemia have an increased frequency and severity of hyperkalaemia in comparison to patients with DKA and preserved renal function. 7 A mainstay of DKA treatment is insulin; this improves both ketonaemia and hyperglycaemia. 5,6 Correction of ketonaemia usually requires ongoing insulin infusion even after normalisation of blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the degree of hypertonicity in dialysis-associated hyperglycemia is predicted by Katz's formula with remarkable accuracy [18]. Urinary potassium losses are also limited, and hyperkalemia is frequent in hyperglycemic episodes occurring in this setting [19][20]. The degree of hyperglycemic hyperkalemia in dialysis patients is higher when ketoacidosis is present [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Ketoacidosis contributes to the development of hyperglycemic hyperkalemia by affecting the function of several transport pathways in the cell membrane [22]. Insulin is the only required treatment for both hyperglycemia and hyperkalemia in patients with ESRD, although additional measures may be necessary for extreme cases of hyperkalemia [19][20]23].…”
Section: Discussionmentioning
confidence: 99%